Learning Management of Kitab Kuning at Pesantren Ashabul Kahfi Surantih Pesisir Selatan Regency West Sumatra - Setiawan, Indil; Kumar, Tribhuwan (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2022)
"Kitab Kuning," as a typical pesantren curriculum, is faced with severe problems due to weak management aspects. This study revealed the "Kitab Kuning" learning plan, implementation, and evaluation. This study was carried out with a qualitative approach and data collection techniques of observation, interviews, and documentation studies. Based on the results, the pesantren did not carry out comprehensive planning; it manifests in teachers teaching the material arbitrarily where learning is carried out every day other than holidays and testing students to read the "Kitab Kuning."